Din Eğitimi ve Sanat: Dini Hikâyelerin Anlatımında Sanatın Rolü. - KABA, Yunus (Burdur Theology Journal / Burdur İlahiyat Dergisi, 2026)
This study aims to examine the relationship between religious education and art, particularly in the context of transmitting religious stories through artistic forms. The main focus of the study is the pedagogical function of artbased approaches in religious education and their contribution to learning processes. The fundamental problem of the research is that traditional methods of religious instruction may not adequately address the attention, interests, and learning styles of new generations shaped by visual culture and digital media. In this context, the study evaluates the contributions of art to religious education through visual arts, auditory arts, performing arts, digital media, and visual culture. It also discusses the role of art in concretizing abstract religious concepts, increasing students’ active participation in the learning process, and making religious narratives more understandable and meaningful. Furthermore, the study emphasizes that art contributes to the internalization of spiritual experiences by developing individuals’ aesthetic sensitivity and emotional awareness. Artistic practices are considered important educational tools that enrich classroom interaction and encourage reflective learning experiences. The research was designed within the qualitative research approach and conducted through the document analysis method. The data sources consist of national and international academic studies published in the fields of religious education, art education, aesthetics, religious narratives, media, visual culture, and digital religion. The collected data were analyzed through descriptive and thematic analysis. The findings reveal that art functions as a multidimensional pedagogical tool in religious education in terms of meaning-making, concretization, emotional engagement, aesthetic experience, empathy, cultural transmission, critical thinking, and digital representation. The results indicate that art is not merely a supplementary element in religious education; rather, it transforms religious narratives into experiential learning processes, deepens understanding, and supports students’ cognitive, emotional, and aesthetic development. This process also contributes to strengthening tolerance toward different beliefs and cultures while improving students’ creative thinking skills and emotional connection with religious content. In addition, digital media tools such as films, animations, digital art, social media, and interactive visual platforms provide important opportunities for transmitting religious stories to younger generations in engaging and accessible ways. In this context, it is considered that art-based religious education practices contribute to students’ development of lasting and meaningful learning experiences. Consequently, the effective use of art in religious education requires a holistic approach that includes pedagogical planning, teacher training, material development, digital media literacy, and cultural and theological sensitivity.